How Smart Technology Affects the Well-Being and Supportive Learning Performance of Logistics Employees? - Jiang, Fei; Wang, Li; Li, Jian-Xin; Liu, Jie (Frontiers in Psychology, 2022)
The COVID-19 outbreak has caused significant changes in employee training, such as in the logistics industry. It has substantially compromised the training activities, leading to a slowdown in learning performance. To meet these challenges, it is necessary to apply effective methods such as smart technology. The study explores the influence of smart technology on corporate trust, self-efficacy and employees' subsequent well-being in learning performance. Respondents (n = 516) comprise employees from ten logistics companies located in China. Smart technology directly affects trust, self-efficacy, well-being, and learning performance. Corporate trust and self-efficacy also directly affect employee well-being and learning performance, which further enhances learning performance. The company's implementation of smart technology usage initiatives may offer positive learning outcomes for employees, such as incremental well-being and excellent learning performance in the firm.